The population of comet candidates among quasi-Hilda objects revisited and updated - Correa Otto, Jorge Alfredo (2023)
In this paper, we perform a dynamical study of the population of objects in the unstable quasi-Hilda region. The aim of this work is to make an update of the population of quasi-Hilda comets (QHCs) that have recently arrived from the Centaurs region. To achieve our goal, we have applied a dynamical criteria to constrain the unstable quasi-Hilda region that allowed us to select 828 potential candidates. The orbital data of the potential candidates were taken from the ASTORB data base and we apply backward integration to search by those that have recently arrived from the outer regions of the Solar system. Then we studied the dynamical evolution of the candidates from a statistical point of view by calculating the time-averaged distribution of a number of clones of each candidate as a function of aphelion and perihelion distances. We found that 47 objects could have been recently injected into the inner Solar system from the Centaur or transneptunian regions. These objects may have preserved volatile material and are candidates to exhibit cometary activity.